2016
DOI: 10.17058/cinergis.v18i1.7903
|View full text |Cite
|
Sign up to set email alerts
|

Dor lombar em mulheres sedentárias e praticantes de musculação

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4. INTRODUÇÃOA dor lombar (DL) é uma situação comum nas sociedades industrializadas, constituindo-se em problema de saúde pública e incapacidade, principalmente para a população economicamente ativa.1 Evidências de qualidade moderada apresentaram que, em qualquer região do Brasil, um em cada quatro brasileiros mais velhos sofrem de dor lombar. 2Por mais comum que seja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Notably, 94% of the participants in this study did not engage in exercise, and despite there being no apparent relationship between physical exercise, pain, and disability, research has demonstrated an important association between a sedentary lifestyle and CLBP 21 . Evidence shows that the level of physical activity influences pain intensity, indicating that sedentary or insufficiently active individuals report higher pain intensity compared to those who are active and very active 22 .…”
Section: Discussionmentioning
confidence: 66%
“…Notably, 94% of the participants in this study did not engage in exercise, and despite there being no apparent relationship between physical exercise, pain, and disability, research has demonstrated an important association between a sedentary lifestyle and CLBP 21 . Evidence shows that the level of physical activity influences pain intensity, indicating that sedentary or insufficiently active individuals report higher pain intensity compared to those who are active and very active 22 .…”
Section: Discussionmentioning
confidence: 66%